Are coalminers, with low "risk factors" for ischaemic heart disease at greater risk of developing progressive massive fibrosis?. Issue 3 (August 1982) - Cochrane, A L; Moore, F; Moncrieff, C B
Abstract : Coalminers with "A" shadows (the first stage of progressive massive fibrosis (PMF)) have a similar standardised mortality ratio (SMR) to those without PMF, and those with A shadows have a much higher specific mortality from pneumoconiosis. It is therefore argued that either A shadows confer immunity against some other disease(s) or that those developing A shadows are selected on the basis of increased life expectancy. These two hypotheses were investigated and as the selection hypothesis appeared promising further studies were made to discover which specific cause of death might be associated with this selection. This, surprisingly, appeared to be ischaemic heart disease.